Effect of modern analgesic drugs (tramadol, pentazocine, and buprenorphine) on the bile duct sphincter in man. Issue 5 (May 1986) - Staritz, M; Poralla, T; Manns, M; Meyer Zum Büschenfelde, K H
Abstract : Modern narcotic analgesic drugs, such as tramadol, pentazocine, and buprenorphine share similarities of molecular structure with morphine which is widely believed to cause spasm of the bile duct sphincter and so impede bile flow. This study assessed the effects of intravenously administered analgesics on bile duct sphincter motor activity measured by ERCP manometry. Ten minutes after pentazocine injection the duration of contractions and baseline pressure of the bile duct sphincter rose from 6.2 +/- 0.2 to 8.2 +/- 0.27 s and from 5.1 +/- 0.6 to 8.8 +/- 0.4 mmHg respectively. Tramadol, buprenorphine and saline showed no such effect. These data indicated that the effects of such drugs on bile duct sphincter function can be safely assessed by ERCP manometry and that pentazocine adversely affects the bile duct sphincter, whilst tramadol and buprenorphine do not. We consider therefore that pentazocine is not the premedication of first choice for endoscopic procedures involving the sphincter of Oddi and should also be avoided in patients with pancreatic and biliary disorders.